PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP RSKG (RUMAH SAKIT KHUSUS GERIATRI) TEJA HUSADA KEPANJEN - Sholichah, Fatmawati (Program Studi Keperawatan dan Kesehatan, Sekolah Tinggi Ilmu Kesehatan (STIKES) Bhakti Al-Qodiri, 2020)
One effort to create a healthy Indonesia is to improve the quality of services and facilities by health providers such as health centers, hospitals and clinics in Indonesia. Hospitals providing health services in Indonesia should be managed properly, in improving the quality of services. In this study, the population was patients who were undergoing treatment at the Teja Husada Kepanjen General Hospital, as many as 105 patients. This random sampling is called Simple Random Sampling. In sampling according to Husein Umar (2003:141) Slovin formula was used. So that the sample taken was 51 respondents. From the research results it can be seen that 1) From the research results it can be seen that service quality variables which include reliability (X1), responsiveness (X2), certainty (X3), empathy (X4), physical evidence (X5) simultaneously affect patient satisfaction RSKG (Geriatric Special Hospital) Teja Husada Kepanjen at RSKG (Geriatric Special Hospital) Teja Husada Kepanjen; 2) From the research results it can be seen that the service quality variables which include reliability (X1), responsiveness (X2), certainty (X3), empathy (X4), physical evidence (X5) have a partial effect on patient satisfaction of RSKG (Geriatri Special Hospital ) Teja Husada Kepanjen at RSKG (Geriatric Special Hospital) Teja Husada Kepanjen; and 3) From the results of the study it can be seen that responsiveness which is one of the service quality variables has a dominant influence on the satisfaction of the Teja Husada Kepanjen RSKG (Special Geriatric Hospital) patients at the Teja Husada Kepanjen RSKG (Geriatric Special Hospital). Keywords: Service Quality, Patient Satisfaction